Ojibwa lexicon - Grafstein, A. (Ann); Piggot, G. L., 1942- (Book collections on Project MUSE., 1983)
Provides data on a range of Ojibwa dialects. Contains two sorted versions of the dictionary: one in the standard sort from left to right and one in a reverse sort from right to left.